2016
DOI: 10.1016/j.micres.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Localization and characterization of two putative TMH family proteins in Chlamydia psittaci

Abstract: Chlamydia psittaci (C. psittaci), an obligate intracellular agent of psittacosis, causes an atypical pneumonia in humans. The transmembrane head proteins (TMH) of C. psittaci, putatively belong to the Inc family and presumably play similar roles. CPSIT_0844 and CPSIT_0846 were the putative TMH proteins of C. psittaci. To identify these two proteins, antisera were raised with fusion proteins which were prokaryotic expressed in Escherichia coli and purified. By immunofluorescence assay, CPSIT_0844 and CPSIT_0846… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Eight tmh genes are found in the C. psittaci genome, and two of them have been shown experimentally to localise to the inclusion membrane later than 18‐hr p.i. (Voigt et al, ; Wu et al, ). Whether TMH or Inc proteins are involved in recruiting CERT to the C. psittaci inclusions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Eight tmh genes are found in the C. psittaci genome, and two of them have been shown experimentally to localise to the inclusion membrane later than 18‐hr p.i. (Voigt et al, ; Wu et al, ). Whether TMH or Inc proteins are involved in recruiting CERT to the C. psittaci inclusions remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…CPSIT-0594 encodes protein IncA. CPSIT-0846 and CPSIT-0844 are two putative transmembrane head protein family proteins which are additionally located in the inclusion membrane, and have been predicted to be type III secretion system (T3SS) effector protein encoding genes (44). Inc proteins may be associated with the processes of inclusion formation, transportation to the nuclear space and evasion of early lysosomal fusion (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…CPSIT_0846 is also a member of the transmembrane head (TMH) protein family, which shares 84% homology with the TMH family protein secreted by C. abortus. We previously found that CPSIT_0846 not only promoted the production of tumor necrosis factor alpha (TNF-a), interleukin (IL)-1b, and IL-6 in human monocytic THP-1 cells in vitro, but also induced a strong humoral and cellular immune response in mice (Wu et al, 2016;Ran et al, 2017). Therefore, we speculate that this protein may be closely related to the pathogenic mechanism of C. psittaci.…”
Section: Introductionmentioning
confidence: 92%
“…Moore and his colleagues found Chlamydial IncA interacted with the G3BP1 partner, and affected the expression of c-myc mRNA, thereby inhibiting host cell apoptosis (Moore and Ouellette, 2014). CPSIT_0846, the homolog of C. psittaci IncA, can be detected at 2 h after host cell infection, and throughout the whole development cycle (Wu et al, 2016). So, CPSIT_0846 may also participates in the pathogenesis of C. psittaci by regulating apoptosis in host cells.…”
Section: Introductionmentioning
confidence: 99%